Variability of Hydro-Meteorological Fluxes in North West Himalayan Basins for Hydrological and Sustainability Studies - Rachit; A. Masiwal; S. Singla; G. Singhal; P. K. Thakur; V. Garg; S. Romshoo; S. Romshoo (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The Himalayas are a crucial source of food, water, and habitat for a wide range of ecosystems in the northern Indian subcontinent. This research focuses on utilizing remote sensing data to analyze hydrological and meteorological factors—such as precipitation, temperature, runoff, evapotranspiration (ET), soil moisture and snow depth—for nine watersheds in the North West Himalayas (NWH): Jhelum, Tawi, Beas, Parbati, Suketi, Gangotri, Aglar, Asan, and Henval. The study employs near real-time (~1-day latency) hydrological flux data from the Famine Early Warning Systems Network (FEWS NET) Land Data Assimilation System (FLDAS) at a spatial resolution of 0.01°. To gain further insights, the trend in snow cover area (SCA) for the NWH region is analyzed using Interactive Multisensor Snow and Ice Mapping System (IMS) data from the United States National Ice Center (USNIC), disseminated by the National Oceanic and Atmospheric Administration (NOAA) via the National Snow and Ice Data Center (NSIDC). The analysis covers water balance components for these basins from 2001 to 2023. Monthly and annual averages are computed to reveal overall watershed behavior and distribution, which is closely linked to the land use and land cover (LULC) in the area. For instance, the Gangotri basin, with over 50% snow coverage, shows low ET throughout the year, a trend reflected in the long-term annual average ET values. Similarly, basins with higher SCA exhibit lower ET percentages, resulting in increased runoff and a strong correlation between rainfall and runoff patterns. A regional analysis of snow cover from 2014 to 2024, encompassing the union territories of Jammu and Kashmir, Ladakh, and the states of Himachal Pradesh and Uttarakhand, indicates a significant decrease in relative SCA. For the peak winter months of December and January, SCA dropped by about 50% from January 2023 (~2,94,635 km2) to January 2024 (~1,48,225 km2). Additionally, the Indian Meteorological Department's (IMD) daily rainfall data for Jammu and Kashmir from December 1, 2023, to January 31, 2024, shows lower rainfall compared to the previous year, likely due to reduced north-west disturbances. This prolonged snow drought poses challenges to water security and increases the risk of wildfire disasters in these regions.